A Quality improvement initiative to reduce central line-associated bloodstream infections in a neonatal intensive care unit in a low-and-middle-income country - Khalid Yunis; Ayah Al Bizri; Rima Hanna Wakim; Alaa Obeid; Tania Daaboul; Lama Charafeddine; Nabil Mounla; Pascale Nakad (BMJ Open Quality)
Background Premature and sick neonates in the neonatal intensive care unit (NICU) are in need of central lines placing them at high risk of contracting a central line-associated bloodstream infection (CLABSI). CLABSI extends length of stay to 10–14 days post negative cultures and increases morbidity, use of multiple antibiotics, mortality and hospital cost. To reduce CLABSI rate at the American University of Beirut Medical Center NICU, the National Collaborative Perinatal Neonatal Network developed a quality improvement project to reduce CLABSI rate by 50% over a 1-year period and to sustain reduced CLABSI rate.Methods Central line insertion and maintenance bundles were implemented for all infants admitted to the NICU necessitating central lines placement. Bundles included hand washing, wearing protective material and sterile drapes during central lines insertion and maintenance.Results CLABSI rate decreased by 76% from 4.82 (6 infections; 1244 catheter days) to 1.09 (2 infection; 1830 catheter days) per 1000 CL days after 1 year. Following the bundles’ success in reducing CLABSI rate, they were incorporated permanently to NICU standard procedure and bundle checklists were added to the medical sheets. CLABSI rate was maintained at 1.15 per 1000 CL days during the second year. It then decreased to 0.66 per 1000 CL days in the third year before reaching zero in the fourth year. In total, zero CLABSI rate was sustained for 23 consecutive months.Conclusion Reducing CLABSI rate is necessary to improving newborn quality of care and outcome. Our bundles were successful in drastically reducing and sustaining a low CLABSI rate. It was even successful in achieving a zero CLABSI unit for 2 years.